Determination of the composition of the Zinelbulak talc-magnesite deposit rock using modern physicochemical methods - Jumaniyazov Maxsud; Kurambayev Sherzod; Atashev Elyor; Jumaniyozov Arslon; Buranova Mokhigul (E3S Web of Conferences)
In this study, the elemental and oxide composition of talc-magnesite raw materials obtained from the Zinelbulak deposit, located in the Sultan Uvays mountain range of Uzbekistan, were investigated using X-ray fluorescence analysis. The results revealed the presence of the following compounds in mass percentages relative to the total mass: talc (3MgO∙4SiO2∙H2O) 60.97%, magnesite (MgCO3) 27.74%, dolomite (MgCO3∙CaCO3) 2.90%, chlorite (5MgO∙5FeO∙Al2(SiO3)3∙H2O) 8.01%, and calcite (CaCO3) 0.38%. The results of the IR spectral analysis of the sample confirm the findings of the X-ray fluorescence and X-ray phase analyses. To further study the composition of the raw material, differential thermal analysis and thermogravimetry methods were employed. A quantitative analysis of particle size during the grinding process of the talc-magnesite raw material from the Zinelbulak deposit was also conducted. The research results indicate the potential for utilizing these new raw material sources in the production of talc and magnesite.